Wykorzystanie metody wzorca rozwoju do rozdziału środków w ramach komponentu regionalnego programu operacyjnego Kapitał Ludzki - Kwiatkowska-Ciotucha, Dorota (Ideal Pattern of Development Method Application for Funds Distribution from Operational Programme Human Capital (Regional Component), 2008)
An attempt of application of linear ordering methods for solving the problem of effective distribution of financial means from European Social Funds (ESF) is presented. The main idea of EU Social Funds is given. The results of the ESF Projects implementation in Poland during the period from 2004 to 2006 are characterized. The proposal leading towards the increase of activities effectiveness in the funds distribution is given. This proposal is based on the idea of the ideal pattern of development method. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 6, s. 26-39